Endometriosis therapy features (clinical lecture) - L A Kovaleva (IP Berlin A.V., 2013)
The following article focuses on endometriosis pathogenesis features as well as on treatment of its clinical manifestations. Endometriosis is defined as the presence of functional endometrial tissue outside the uterus, causing diverse progressive symptoms such as infertility, pelvic pain, and dysmenorrhea.Тhe etiopathogenesis and treatment of endometriosis still remains unknown. Тhe disease can be effectively cured by definitive surgery. However, prolonged medical therapy may be needed in most of the cases since conservative surgery is usually performed especially in young women.